Measurement of the transverse momentum spectra of weak vector bosons produced in proton-proton collisions at s?=8s=8 TeV - Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Asilar, E.; Bergauer, T.; Brandstetter, J.; Brondolin, E.; Dragicevic, M.; Ero, J.; Flechl, M.; Friedl, M.; et al. (My University, 2017)
The transverse momentum spectra of weak vector bosons are measured in the CMS experiment at the LHC. The measurement uses a sample of proton-proton collisions at root s = 8TeV, collected during a special low-luminosity running that corresponds to an integrated luminosity of 18: 4 +/- 0: 5 pb(-1). The production of W bosons is studied in both electron and muon decay modes, while the production of Z bosons is studied using only the dimuon decay channel. The ratios of W- to W+ and Z to W di ff erential cross sections are also measured. The measured di ff erential cross sections and ratios are compared with theoretical predictions up to next-to-next leading order in QCD.
Citation: Khachatryan, V., Sirunyan, A. M., Tumasyan, A., Adam, W., Asilar, E., Bergauer, T., . . . Collaboration, C. M. S. (2017). Measurement of the transverse momentum spectra of weak vector bosons produced in proton-proton collisions at root s=8TeV. Journal of High Energy Physics(2), 44. doi:10.1007/jhep02(2017)096
Keywords: Hadron-Hadron Scattering (Experiments); Qcd; Hadron Colliders; W-Boson; Qcd; Physics